2022
DOI: 10.1155/2022/5588184
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of Mahogany Production in Plantations: Does Resource Availability Influence Susceptibility of Young Mahogany Plantation Stands to Hypsipyla robusta Infestation?

Abstract: Hypsipyla robusta Moore (Lepidoptera: Pyralidae), like many other moth species, shows selectivity when choosing host plants for its eggs. Four Meliaceae species (Khaya grandifoliola, K. ivorensis, Swietenia macrophyla, and Entandrophragma cylindricum) were established in a moist semideciduous forest in Ghana to study this selectivity at 12 and 21 months after planting. The analysis of variance (ANOVA) at a P -value of 0.05 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…For example, a forest inventory conducted in native populations of Mahogany in the province of Pastaza yielded that 93% of the sampled seedlings indicated signs of herbivory in 50% of their leaves [154]. This demonstrates that the species presents a great vulnerability to herbivores that limits its growth and the survival of individuals in its populations [29,30]. Research focused on the phytosanitary control of Mahogany indicated that the most relevant biological threat to the species would be the insect Hypsipyla grandella (Lepidoptera: Pyralidae) [155,156].…”
Section: Model Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a forest inventory conducted in native populations of Mahogany in the province of Pastaza yielded that 93% of the sampled seedlings indicated signs of herbivory in 50% of their leaves [154]. This demonstrates that the species presents a great vulnerability to herbivores that limits its growth and the survival of individuals in its populations [29,30]. Research focused on the phytosanitary control of Mahogany indicated that the most relevant biological threat to the species would be the insect Hypsipyla grandella (Lepidoptera: Pyralidae) [155,156].…”
Section: Model Limitationsmentioning
confidence: 99%
“…This species presents a slow growth, and therefore an ineffective natural regeneration, a period of 30 years being necessary for it to be able to develop completely [28]. In addition, it presents a great vulnerability to climatic conditions that affect its germination or pests that limit its growth [29,30]. For all these reasons, it is considered vulnerable to extinction according to the IUCN evaluation categories and is one of the most threatened forest species in the world [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Salah satu tujuan investor dalam berinvestasi, baik investasi riil pada aktiva berujud maupun investasi keuangan adalah mendapatkan keuntungan di dalam bentuk peningkatan nilai asetnya (Darko et al, 2022;Koesoemasari et al, 2022). Sebagai manusia yang rasional, pilihan investasi yang dilakukan investor adalah investasi yang memberikan return yang tinggi, dengan tentu saja memperhatikan risiko yang menyertai investasi tersebut.…”
Section: Pendahuluanunclassified
“…The larvae of H. robusta bore into the shoot tips and form tunnels in the stem resulting in loss of apical dominance, deformation of the crown, and reduction in merchantable wood (Nuraeni and Nuroniah 2020, Tra et al 2021, Darko et al 2022). Forest companies in Vietnam are concerned because tree height is being reduced by 20–30% in young trees (Chi 2020, Tra et al 2021).…”
mentioning
confidence: 99%
“…Forest companies in Vietnam are concerned because tree height is being reduced by 20–30% in young trees (Chi 2020, Tra et al 2021). Severe damage from shoot-tip borers is a major obstacle to the expansion of plantations of susceptible hosts in many countries (Cunningham et al 2005, Opuni-Frimpong et al 2008, 2022, Darko et al 2022).…”
mentioning
confidence: 99%